A novel near monochromatic red emissive europium(III) metal-organic framework based on 1,2,4,5-benzenetetracarboxylate: From synthesis to photoluminescence studies - Lahoud, Marcelo G. [UNESP]; Frem, Regina C.G. [UNESP]; Marques, Lippy F.; Arroyos, Guilherme [UNESP]; Brandão, Paula; Ferreira, Rute A.S.; Carlos, Luís D. (Elsevier, 2017)
This work presents the synthesis, solid state characterization (infrared spectroscopy, thermal analysis (TGA/DTA), powder and single crystal X-ray diffraction) and photoluminescence studies of a new europium metal-organic framework (MOF), [Eu2(Btec)1,5(H2O)]n (Btec4−=1,2,4,5-benzenetetracarboxylate anion). Single crystal X-ray diffraction analysis reveals that the material has a three-dimensional network, with two crystallographically independent Eu(III) ions adopting different coordination geometries. This structure presents one of the Btec4− anions acting as a μ8-bridging linker, with the carboxylate groups in distinct connection to Eu(III) ions, culminating into an unknown coordination mode for the linker. The results of thermogravimetric analyses indicate that the MOF has high thermal stability, with this characteristic being of great interest for the application of these compounds in several fields such as catalysis and photonics. The luminescent properties showed that the Eu(III) ions are a local-spectroscopic probe, with the compound presenting a red emission when excited in the UV spectral region with absolute emission quantum yield values of 0.48 ± 0.05. The thermal dependence on the intensity of the transitions originating from the 7F1 level, especially the 7F1 → 5D1 transition, was studied. These results opens the possibility to test this MOF [Eu2(Btec)1.5(H2O)]n in the field of molecular thermometry.
Keywords: Europium; Metal-organic frameworks; Photoluminescence; Tetracarboxylate